2022
DOI: 10.1051/mfreview/2021032
|View full text |Cite
|
Sign up to set email alerts
|

Additive manufacturing towards product production: a bibliometric analysis

Abstract: Additively manufactured products offer extensive variety to consumers than many forms of production. Additive manufacturing (AM) production system allows consumer involvement, which has created a huge but largely untapped market. However, there is a gap between production and the market. Therefore, AM towards product production which focuses on the Commercialization of Additive Manufactured Products (CAMPs) is imperative. Despite the importance of CAMP, specific focus of research on the commercialization of ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…The research indicators are key in identifying the significance of any research area. The influence of authorship, co-authorship, regions by countries, affiliations (or institutions), publication sources, and keywords are some of the aspects that are taken into account in the formulation of the scientometric investigation or similar bibliometric reviews [ 88 , 89 , 90 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 ]. Some mapping was conducted on the publication data retrieved using VoS Viewer [ 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 ], using standard methods of bibliometric mapping [ 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The research indicators are key in identifying the significance of any research area. The influence of authorship, co-authorship, regions by countries, affiliations (or institutions), publication sources, and keywords are some of the aspects that are taken into account in the formulation of the scientometric investigation or similar bibliometric reviews [ 88 , 89 , 90 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 ]. Some mapping was conducted on the publication data retrieved using VoS Viewer [ 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 ], using standard methods of bibliometric mapping [ 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 ].…”
Section: Methodsmentioning
confidence: 99%
“…A consensus-based debate on the results of the scientometric review study led to the classification structure of research subjects in these two areas. It was reported that Nalimov and Mulchenko coined the word “Scientometrics” for the first time in 1969 as an evaluation of science [ 88 , 89 , 94 , 95 ]. From the second half of the 19th century to the present, scientometrics has been a growing field of study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other benefits include low-volume production and the facilitation of personalized and customized products, in addition to low-cost production and less dependence on expensive and dedicated tooling [ 25 , 26 ]. Responsive production, shorter supply chains, democratization of production, reduction of the environmental impact due to less waste production as well as increased preparedness for the digital revolution are other advantages of additive manufacturing [ 27 ]. Due to the versatility of the AM technology to produce customized 3D structures, it is one of the advanced manufacturing technology which is currently used to provide medical devices to fight the covid-19 pandemic [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additive manufacturing (AM) technology is gradually attaining maturity and being used to produce end-user products [6,[20][21][22]. The technology could be used to produce biomedical objects monolithically with tailored geometrical configurations as opposed to the conventional methods [23,24].…”
Section: Introductionmentioning
confidence: 99%